2020
DOI: 10.1037/cdp0000287
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of pubertal timing relative to peers: Comparison targets and social contexts of comparison.

Abstract: Objectives: In studies measuring pubertal timing multiple ways, perceived timing relative to peers is more strongly associated with adverse outcomes in girls. However, girls’ comparison targets (those to whom they compare) and the contexts in which comparison occurs is unclear. This study examined perceived relative pubertal timing to identify the comparison target (ethnicity-race) and the contexts (schools, neighborhoods) of these comparisons. Method: We assessed perceived relative pubertal timing in a divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
0
8
0
1
Order By: Relevance
“…However, extant research has also demonstrated inconsistent group differences on social anxiety between early and later maturers (Blumenthal et al, 2009; Deardorff et al, 2007). Further, evidence suggests that adolescents’ perceptions of their development relative to their peers are more significant for mental health than actual morphological changes (Carter et al, 2019) and hence our measure might not have been sufficiently sensitive. More importantly, the age of the current cohort was relatively young, both for the development of social anxiety disorder and for pubertally related morphological changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, extant research has also demonstrated inconsistent group differences on social anxiety between early and later maturers (Blumenthal et al, 2009; Deardorff et al, 2007). Further, evidence suggests that adolescents’ perceptions of their development relative to their peers are more significant for mental health than actual morphological changes (Carter et al, 2019) and hence our measure might not have been sufficiently sensitive. More importantly, the age of the current cohort was relatively young, both for the development of social anxiety disorder and for pubertally related morphological changes.…”
Section: Discussionmentioning
confidence: 99%
“…While the hormonal changes associated with puberty underpin changes in brain development and can impact sleep and emotional reactivity, many of the morphological changes can impact on self-concept and social interactions (Boxer et al, 1983). Early developing youth compare themselves against their immediate peer group (Carter et al, 2019) and often perceive themselves to be discordant with respect to appearance (Vogt Yuan, 2007). In turn, early pubertal development (relative to peers) is associated with greater levels of peer-related stress (Conley et al, 2012) and has consistently been linked to a range of mental disorders, especially in girls (Ullsperger & Nikolas, 2017).…”
mentioning
confidence: 99%
“…Es decir, en general podrían estar insatisfechos con sus vidas. Esto refleja la sensación generalizada de insatisfacción que es tan típica de la depresión (Carter et al, 2020;Lewinsohn et al, 1991). El resultado del estudio actual es consistente con investigaciones previas, en el sentido de que se encontró una relación entre las variables (Baruah & Hussain, 2021;Cook, 2003;Ried et al, 2006).…”
Section: Discussionunclassified
“…Our understanding of our own development is significant in comparison with those around us. Analyses of pubertal development exploring the social comparison that occurs when individuals self-report pubertal development (Carter, Blazek, & Kwesele, 2020; Mendle, Beltz, Carter, & Dorn, 2019; Thompson et al, 2016) provide support for models that measure perceptions of pubertal onset in addition to stage.…”
Section: Discussionmentioning
confidence: 99%